Thinking System for Forming and Monitoring the Scientific Rating of Professor Teachers Online - M, Salimova; D., Mingboyeva (European Journal of Life Safety and Stability (2660-9630), 2021)
If we look at the example of online monitoring of teacher ratings in the article, we can say that to date, there are very few, if any, online teacher software tools. Taking into account this requirement, a simulator with a clear and user-friendly interface will be developed among professors and teachers, including students and teachers of higher education institutions. For the formation of this rating system and the design of the simulator, special attention is paid to the placement of resources in 4 modules, the formation of monitoring, calculation of ratings on the basis of special and standard scales, filtering reports and improving mechanisms.